Systematic Characterization of Expression Profiles and Prognostic Values of the Eight Subunits of the Chaperonin TRiC in Breast Cancer - Xu, Wen-Xiu; Song, Wei; Jiang, Meng-Ping; Yang, Su-Jin; Zhang, Jian; Wang, Dan-Dan; Tang, Jin-Hai (Frontiers in Genetics, 2021)
Background: Chaperonin-containing TCP-1 (TRiC or CCT) was demonstrated to be involved in in oncogenesis of cancers carcinogenesis and development of various malignancies. Increasing experimental evidence indicated that dysregulation of TRiC was implicated in the tumor progression of breast cancer (BCa). However, few definitive studies have addressed the diverse expression patterns and prognostic values of eight TRiC subunits. Thus, we aimed to investigate the clinical significance of TRiC subunit expression and prognostic values for their possible implications in diagnosis and treatment. of BCa. Methods: Based on updated public resources and comprehensive bioinformatics analysis, we used some online databases (eg, UALCAN, GEPIA, cBioPortal, TIMER, BC-GenExMiner, metascape and GeneMANIA) to comprehensively explore the expression levels and the prognostic effects of eight TRiC subunits in patients with BCa. Results: The transcriptional levels of most subunits of the Chaperonin TRiC (CCT2, CCT3, CCT4, CCT5, CCT6A and CCT7) were significantly elevated compared with normal breast tissues, whereas TCP1, CCT4 and CCT6B were lower in BCa tissues than in normal tissues. Besides, copy number alterations (CNA) of eight TRiC subunits positively regulated their mRNA expressions. Furthermore, high mRNA expression of TCP1/CCT2/CCT4/CCT5/CCT6A/CCT7/CCT8 was significantly associated with poor overall survival (OS) in BCa patients. The eight subunits of the chaperonin TRiC was related to tumor purity and immune infiltration levels of BCa. Co‐expression analysis showed CCT6B was negatively associated with other subunits of TRiC and other subunits of TRiC were positively correlated with each other. Additionally, TRiC and their interactive proteins were correlated with positive regulation of biological process, localization and biological regulation. Conclusion: This study systematically illustrated the expression profiles and distinct prognostic values of chaperonin TRiC in BCa, providing insights for further investigation of subunits of the chaperonin TRiC as novel therapeutic targets and potential prognostic biomarkers in BCa.